(untitled) (Huellas, 2017)
This article analyzes the processes and contexts of olive growing in San Rafael, Mendoza, from the year 2000 onwards, during the periods of boom, fall and stagnation caused by climate scourges and by structural and current processes related to international, national and local contexts. These processes and their consequences will make it possible to understand the latest transformations in the sector and the possible perspectives of this regional production process, and to improve the knowledge of its tensions and fluctuations. On the basis of the theoretical framework of the regional economies, we consider the fluctuations that the activity undergoes and that depends not only on the environmental features but also on institutional, economic, historical, cultural and social aspects with all the asymmetries involved in the development of each one of them. For this purpose, primary and secondary sources were used, such as legislation related to the activity, interviews with key referents, statistics, scientific articles and journals and local and provincial newspapers.